Interrogating peace in a violent democracy: a global south critique - Buer, Ingri Bøe; Villenave, Sabrina (Frontiers in Political Science, 2024)
This article examines the complex and often conflicting forms of ‘peace’ in Rio de Janeiro’s favelas, using a postcolonial critique to challenge the state’s top-down imposition of realist and neoliberal peace models. It begins by interrogating the concept of ‘peace’ in the context of the Brazilian State’s historical racialization and criminalization of favelas. The article develops four key arguments. First, it considers how militarized public security policies in the “War on Drugs” translate into ‘peace as war’ in the favelas. Second, it considers criminal governance as ‘peace as order’. Third, it critiques the Pacifying Police Program (UPP) as part of a neoliberal ‘tourist peace,’ prioritizing the safety of international visitors during significant events in 2014 and 2016. Finally, it highlights non-violent peace processes within the favelas, which aim to achieve a ‘positive peace.’ The article argues that different actors, including organized criminal groups, can produce various forms of peace, raising critical questions about whose peace is being pursued and at what cost.